2022
DOI: 10.1111/1471-0528.17117
|View full text |Cite
|
Sign up to set email alerts
|

Maternal liver dysfunction in early pregnancy predisposes to gestational diabetes mellitus independent of preconception overweight: A prospective cohort study

Abstract: Objective: To evaluate whether the associations of maternal liver dysfunction and liver function biomarkers (LFBs) with gestational diabetes mellitus (GDM) are independent of overweight. Design: Prospective cohort study.Methods: A sub-cohort of pregnant women with seven LFBs examined at 9-13 weeks of gestation and with complete GDM evaluation at mid-gestation were extracted from the prospective Shanghai Preconception Cohort Study. Associations of liver dysfunction, defined as having any elevated LFB levels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
6
10
1
Order By: Relevance
“…Prior studies have examined the association of liver enzyme levels and its development of adverse pregnancy outcomes, such as GDM and pre-eclampsia. [16][17][18][19][20] By itself, liver enzyme levels, such as ALT, are poor predictors of MAFLD. 21 As such, non-invasive indices of hepatic steatosis may be a simple measure (over imaging) used to assess for probable MAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have examined the association of liver enzyme levels and its development of adverse pregnancy outcomes, such as GDM and pre-eclampsia. [16][17][18][19][20] By itself, liver enzyme levels, such as ALT, are poor predictors of MAFLD. 21 As such, non-invasive indices of hepatic steatosis may be a simple measure (over imaging) used to assess for probable MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on liver enzymes collected either pre-gravid 16,17 or during pregnancy. [18][19][20] The inclusion of pre-gravid AST and ALT in our study was important as prior studies have determined that abnormal values were associated with the development of adverse maternal outcomes, such as GDM or pre-eclampsia. 16,17 Whilst a majority of studies analysed liver enzyme levels during pregnancy and determined associations with adverse pregnancy outcomes, [18][19][20] liver enzyme levels can change during the course of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, imaging examinations or diagnoses of liver steatosis and cholestasis are not available in our study. Several observational studies have reported the signi cant association of maternal GGT and ALP levels in early pregnancy with the development of gestational diabetes between 24-28 gestation weeks 32,33 . Our novel ndings add new evidence to the relationship between maternal GGT, ALP levels, and SPL risk, and provide a clue that maternal liver steatosis or cholestasis maybe two of the possible underlying mechanisms for the development of SPL.…”
Section: Discussionmentioning
confidence: 99%
“…The liver, a target organ of IR-related diseases such as GDM and T2DM, exhibits dysfunction in the early pregnancy, which can increase the risk of GDM in the pregnancy period [12,13].…”
Section: Introductionmentioning
confidence: 99%